CULTIVATING GROWTH AND COMPETITIVENESS OF BREADFRUIT (ARTOCARPUS ALTILIS) AS ALTERNATIVE FOOD DIVERSIFICATION AND STAPLE FOOD SUBSTITUTION IN INDONESIA - Haruming Sekar Saraswati (Proceedings International Indonesia Conference on Interdisciplinary Studies, 2025)
This qualitative research elaborates the potentials, obstacles, and challenges in cultivating breadfruit (Artocarpus altilis) or sukun as a staple food alternative in Indonesia. Data collections were conducted by in-depth interviews, field observation, and literature reviews. Breadfruit serves a promising business potentials in Indonesia, since it can be processed into various products, such as flour, crackers, and many others such as brownies and fermented goods. Breadfruit is also a superfood which provides beneficial nutrients as a source of healthy food. No wonder that breadfruit, with its 80% of carbohydrate, is a very potential alternative for staple food in Indonesia, despite not yet very popular in replacing rice. For the Indonesian farmers, breadfruit is also convenient to grow, as it can be planted in various types of land, and it can be harvested twice a year. Research found that farmers only need 10 breadfruit trees to grow, and they can earn IDR 20 million / USD 1220 for each harvest. On the other hands, this study identifies the obstacles in developing breadfruit in Indonesia, such as agricultural technical obstacle where breadfruit is prone to rottenness and damage due to containing high level of water (60-80%); the dependency to seasons and price fluctuations; the suboptimum marketing infrastructure; the agricultural institution in Indonesia which doesn’t function optimally; and limited use of breadfruit among people. In order to solve these problem, this research recommends several aspects to improve, such as management, marketing, and infrastructure; and specifically by implementing product innovation development, food processing quality improvement, and stronger institutional supports in food sector.